Macroinvertebrata Recruitments in Artificial Reef After Two Years of Sinking on The Damas Beach, Trenggalek - Shafa Thasya Thaeraniza; Oktiyas Muzaky Luthfi; Andik Isdianto (Journal of Marine and Coastal Science, 2020)
The condition of coral reefs in Damas Beach is included in the bad category because there are many fragments of coral reefs (rubble) caused by fishing nets caught in the reef. Based on the problem of coral reefs contained in the waters of Damas Beach, there are innovations to sink artificial reefs. The condition of artificial reefs that have been derived in the waters of Damas Beach within 2.5 years needs to be monitored to find out the macroinvertebrates that stick to the artificial reefs. Retrieval of macroinvertebrate data using the underwater photo transect method with the help of underwater cameras to produce observational data. The results found 10 types of macroinvertebrates with a total of 9,293 individuals. The composition of attached macroinvertebrates is dominated by barnacles by 66% and the density of macroinvertebrates is dominated by barnacles by 4.50 ind / m² out of a total density of 6.88 ind / m².